Troxerutin, a Bioflavonoid Exhibits Oxidative Stress-induced Cytotoxic Effects on KB Cells - Tan, Li; Ding, Huanping; Xi, Haimeng (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: The prevalence of oral cancer is high and it is the sixth most occurring cancer in the world. Some of the drugs used to treat oral cancer cause adverse effects and are resistant to treatment. Objectives: This study was designed and performed to evaluate the cytotoxic and anti-cancerous effects of troxerutin. Materials and Methods: Cell proliferation, cell viability, and morphological analysis were performed with different doses of troxerutin. Once the IC50 value was obtained, doses were fixed and nitric oxide and lipid peroxidation were measured. Qualitative analysis of ROS and mitochondrial membrane potential was performed using 2′,7′-dichlorofluorescein methods and rhodamine 123 fluorescent staining respectively. Results: Troxerutin caused cytotoxicity and reduced cell viability. The IC50 value was 50 μg/ml. Morphological analysis revealed KB cells suffered after troxerutin treatment. Nitric oxide and TBARS levels were elevated. ROS concentration increased and mitochondrial membrane potential diminished with a higher concentration of the drug. Conclusion: Troxerutin exhibits an anti-cancer effect and can act as a NO-donating and ROS-promoting compound aiding in chemotherapy.
Keywords: Oral cancer; Troxerutin; Nitric oxide; Oxidative stress; Anti-cancer; Chemotherapy